Firdaws al-Na'īm: Tradisi Tafsīr Klasik dalam Konteks Lokal Madura - Ihwan Agustono; Muhammad Badrun; Rif’at Husnul Ma’afi; Putri Alfia Halida (Universitas Darussalam Gontor, 2025)
This study examines the tafsīr method of Firdaws al-Na'īm by Thaifur Ali Wafa, which represents a significant contribution to the development of contemporary tafsīr in Indonesia. This method integrates classical tafsīr traditions with a contextual approach relevant to local social and cultural issues, particularly in Madura. The main focus of this research is to analyze how Firdaws al-Na'īm combines the text of the Qur'ān with the cultural values of Madura and its contribution to addressing the modern challenges of Muslim life in Indonesia. Using a qualitative approach based on library research, this study compares Firdaws al-Na'īm with classical tafsir works such as Tafsīr al-Qhurtūbī, al-Nasāfī, al-Jalālayn, and Mafātih al-Ghayb. The findings reveal that Firdaws al-Na'īm offers a tafsīr that is not only theoretical but also practical, considering the social and cultural context. This method enriches the tafsīr tradition in Indonesia and provides a new, relevant perspective for contemporary Muslim life